Comparison of Glasgow Blatchford and New Risk Scores to Predict Outcomes in Patients with Acute Upper GI Bleeding - Bahadır TAŞLIDERE; Elmas BİBERCİ KESKİN; Serdar ÖZDEMİR; Ahmet ATSIZ; Ertan SÖNMEZ (Bezmiâlem Science, 2023)

(untitled)
Objective:Upper gastrointestinal (GI) bleeding constitutes a significant number of admissions to the emergency department, and it has high rates of morbidity and mortality. In this study, the contribution of new scores, such as The International Bleeding Risk Score (ABC score) and the Horibe GI bleeding prediction score (HARBINGER), to clinical practice was investigated. Using scores that are easy to calculate and memorable when used in the emergency department enables a more efficient use of medical resources. In addition, it may contribute to solving the problems regarding determining the need for intensive care in patients with upper GI bleeding.Methods:This study was conducted retrospectively on patients over the age of 18 who were admitted to the emergency department between September 1, 2018 and August 31, 2019. The HARBINGER and ABC scores and the Glasgow Blatchford score (GBS) were calculated for each patient. Following that, the need for intensive care, mortality, re-bleeding rate, and transfusion need were compared.Results:This study included 184 patients. When predicting the need for intensive care, the ABC score had a higher AUC value than the GBS and HARBINGER score, even when there was a low cut-off value (cut-off value >4). (AUC =0.944, specificity =0.74, sensitivity =0.83).Conclusion:This study found that the ABC score could be used to predict the need for intensive care in upper GI bleeding, and that it outperformed other scores. Additionally, we concluded that the HARBINGER score, which had a “shock index” among its parameters, was not effective in predicting in-hospital adverse events.